Perfil epidemiológico e fatores associados à síndrome respiratória aguda grave em Goiás, no período de 2013-2018 - Araujo, Kamilla Lelis Rodrigues de (2020)
Severe Acute Respiratory Syndrome (SARS) is a condition that, in addition to classic symptoms of influenza, shows signs of worsening with high morbidity and mortality. Thus, is a major concern for public health, being a disease of epidemiological importance, thatmust be notified and investigated. Therefore, the aim of this study was analyze the epidemiological profile and associated factors of SARS reported in the state of Goiás, between 2013 to 2018. This is a retrospective cohort study, with data obtained from the National disease notification system - Influenza Web. Logistic regression analysis was performed to verify the association between death and ICU admission and exposure variables by using the SPSS 25.0 statistical package program. Between 2013 and 2018, 4,832 cases of SARS were reported in Goiás. During the analyzed period, the majority of cases was attributed to Influenza virus (A or B), mainly Influenza A (22.3%), with predominance of pandemic H1N1 Influenza 2009 subtype H1N1pdm09 (17,9%). Among the variablesrelated to ICU admission, longer time to start antiviral treatment in days wasassociated with an increase in hospitalization while the absence of previousinfluenza vaccination, longer time to start antiviral treatment and older age wereassociated with deaths. Thus, this study showed a high frequency of SARS in the state of Goiás between the years 2013 and 2018, with the Influenza A virus(H1N1pdm09) being the main etiological agent. Among the factors related toadmission to the ICU and death, the time of initiation of treatment with antiviral, vaccination status and age of the patientwere observed, which highlights theneed for constant monitoring of the epidemiological situation of this disease, inorder to adopt public health measures for prevention and control.